The Impact of Job Analysis, Job Design, and Training on Employee Performance at Companies in Jakarta - Bharata, Andhi; Ramdhani, Rani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Each organizational unit requires reliable human resources to perform its tasks efficiently and achieve strategic goals. Productive and consistent employees are essential because human resources represent the core competency that determines a company’s sustainable competitive advantage. This study aims to examine the effect of Job Analysis, Job Design, and Training on Employee Performance in several companies located in Jakarta. The research focuses on understanding how each independent variable influences the dependent variable and the overall contribution of human resource practices to performance improvement. A quantitative approach was used, and data were collected through a structured questionnaire distributed to one hundred employees from various companies. The responses were analyzed using IBM SPSS Statistics 23, employing regression analysis to test the proposed hypotheses. The findings reveal that Job Analysis, Job Design, and Training each have a positive and significant impact on Employee Performance. This indicates that a clear understanding of job roles, well-structured job design, and effective training programs can enhance employee productivity and organizational efficiency. The study emphasizes the importance of strategic human resource management practices as a key driver in improving employee outcomes and sustaining business performance in competitive urban environments like Jakarta.